2004
DOI: 10.1128/iai.72.7.3777-3782.2004
|View full text |Cite
|
Sign up to set email alerts
|

ITIH4 (Inter-Alpha-Trypsin Inhibitor Heavy Chain 4) Is a New Acute-Phase Protein Isolated from Cattle during Experimental Infection

Abstract: We have isolated from calf serum a protein with an apparent M r of 120,000. The protein was detected by using antibodies against major acute-phase protein in pigs with acute inflammation. The amino acid sequence of an internal fragment revealed that this protein is the bovine counterpart of ITIH4, the heavy chain 4 of the inter-alpha-trypsin inhibitor family. The response of this protein in the sera was determined for animals during experimental bacterial and viral infections. In the bacterial model, animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 43 publications
2
69
2
1
Order By: Relevance
“…Thus far, numerous studies have shown involvement of ITIs in various pathological processes, including formation of urinary tract stones (Atmani and Khan, 1999;Janssen et al, 2001), female infertility (Zhuo et al, 2001), atherosclerosis and vascular disease (Onda et al, 1999;Fujita et al, 2004), and inflammation (Balduyck et al, 2000;Yingsung et al, 2003;Pineiro et al, 2004). Furthermore, several lines of evidence suggest a potential role of ITIs in tumour biology, particularly in the metastatic cascade and tumour progression (Kobayashi et al, 1995;Bourguignon et al, 1999;Paris et al, 2002;Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, numerous studies have shown involvement of ITIs in various pathological processes, including formation of urinary tract stones (Atmani and Khan, 1999;Janssen et al, 2001), female infertility (Zhuo et al, 2001), atherosclerosis and vascular disease (Onda et al, 1999;Fujita et al, 2004), and inflammation (Balduyck et al, 2000;Yingsung et al, 2003;Pineiro et al, 2004). Furthermore, several lines of evidence suggest a potential role of ITIs in tumour biology, particularly in the metastatic cascade and tumour progression (Kobayashi et al, 1995;Bourguignon et al, 1999;Paris et al, 2002;Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative alteration of the fragments of inter-a trypsin inhibitor, heavy chain H4 was previously found to be associated with various cancer diseases, [22][23][24] indicating that the alteration of these species is not specific to MDS. Inter-a trypsin inhibitor, heavy chain H4 has been shown to be a positive acute phase protein in human and other animals, [25][26][27] thus the increase of these species might be associated with the inflammatory processes ongoing in MDS. 28 We also detected Proteomic analysis of serum proteome of myelodysplastic syndromes C Chen et al changes in transferrin, variants of transthyretin and haemoglobin a-and b-chains in diseased samples.…”
Section: Discussionmentioning
confidence: 99%
“…This protein was also referred to as PK-120 [26] or IHRP [36] being subsequently denominated ITIH4 (heavy chain 4 of the inter-alpha trypsin inhibitor family) [5]. Increases in the ITIH4 concentration under different physio-pathological situations have been reported in pigs [18,21,38], rats [10,17], bovines [30], humans [29,43] and mice [12]. In addition, we have previously reported that apolipoprotein A-I (apo A-I), the major protein component of high density lipoprotein (HDL), shows prominent decreases during experimental bacterial infection and acute inflammation [7,25].…”
Section: Introductionmentioning
confidence: 99%